2010
DOI: 10.1111/j.1365-2761.2010.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and distribution of granulomatous inflammation in freshwater ornamental fish infected with mycobacteria

Abstract: Mycobacteriosis in fish is a chronic progressive ubiquitous disease caused by Mycobacterium marinum, M. gordonae and M. fortuitum in most cases. The aim of this study was to describe the morphology and distribution of lesions in 322 freshwater ornamental fish across 36 species. Granulomatous inflammation was diagnosed by gross examination and histopathology testing in 188 fish (58.4%); acid-fast rods (AFR) were determined in only 96 (51.1%) fish from 19 species after Ziehl-Neelsen staining. The most often affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 20 publications
8
53
0
Order By: Relevance
“…Mycobacteriosis of aquarium fish in the Czech Republic is one of the most commonly diagnosed bacterial diseases (Navratil et al, 2000;Novotny et al, 2004). Gross changes may include emaciation, ascites, exophthalmos, and keratitis, changes in pigmentation and skin ulcerations (Wolf and Smith, 1999).…”
Section: Bacterial Pathogens Transmissiblementioning
confidence: 99%
“…Mycobacteriosis of aquarium fish in the Czech Republic is one of the most commonly diagnosed bacterial diseases (Navratil et al, 2000;Novotny et al, 2004). Gross changes may include emaciation, ascites, exophthalmos, and keratitis, changes in pigmentation and skin ulcerations (Wolf and Smith, 1999).…”
Section: Bacterial Pathogens Transmissiblementioning
confidence: 99%
“…In this study, in fish which revealed no visible pathomorphological granulomatous changes, the mycobacteria were found through direct microscopy and bacteriological exami-nation. Severe systemic mycobacteriosis without typical granuloma formation was diagnosed by Yanong et al (32) in a group of six mature captive striated frogfish (Antennarius striatus), and by Novotny et al (21) in three-spot gourami (Trichogaster trichopterus). The presence and distribution of mycobacterial species in clinically healthy aquarium fish and their environ-ment has been also noted by Beran et al (5) and Zanoni et al (33).…”
Section: Discussionmentioning
confidence: 97%
“…Fish mycobacteriosis is well-recognised in marine and freshwater fish, with several reviews concerning the topic (6,7,12 (1,7,13,32). Environmental mycobacteria can be pathogenic to a variety of freshwater and marine fish species both in the wild and kept in captivity (15,21) (3,13,20,22,29). Clinical signs of fish mycobacteriosis are quite variable and usually include loss of appetite, lethargy, staying alone in the corner of the aquarium, floating on the surface of the water, anorexia, skin discoloration, open lesions, ulcerations, unilateral or bilateral exophthalmia, emaciation, skeletal deformities, and well-demarcated granulomas in internal organs (7,25).…”
Section: Introductionmentioning
confidence: 99%
“…Human infection may be caused by direct injury by fish fins or occur after a cutaneous trauma and exposure to contaminated water. 11 Due to its low culture temperature and inhibition of growth at 37°C, the infection is mostly limited to the skin, though it may also reach deeper structures. 12 The mean incubation period is 7 months.…”
Section: Discussionmentioning
confidence: 99%